MODERN TECHNOLOGIES, FORMS, AND METHODS OF TEACHING MEDICO PREVENTIVE ORIENTED ACADEMIC DISCIPLINES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The modernization of medical education requires the implementation of advanced pedagogical approaches that ensure the effective formation of preventive competencies among future healthcare professionals. This study aims to analyze modern technologies, instructional forms, and teaching methods applied in the delivery of medico-preventive oriented academic disciplines. The analysis is based on contemporary educational models integrating digital technologies, interactive learning formats, and competency-based approaches in medical and public health education. Particular attention is given to the role of simulation technologies, problem-based learning, blended and distance education, and digital educational platforms in enhancing student engagement and professional readiness. The findings indicate that the integration of innovative teaching technologies with traditional instructional methods significantly improves knowledge retention, critical thinking skills, and practical competence in preventive medicine. Furthermore, the use of interdisciplinary and practice-oriented teaching formats supports the development of analytical and decision-making abilities essential for medico-preventive activities. The results emphasize that modern educational technologies and methods are key drivers in improving the quality of training in medico-preventive disciplines and contribute to the alignment of medical education with current public health challenges.
Keywords: Medical education; preventive medicine; teaching technologies; instructional methods; competency-based learning; digital education.